Sensitivity of simulated water mass transformation on the Antarctic shelf to tides, topography and model resolution - Boeira Dias, Fabio; Rintoul, Stephen R.; Richter, Ole; Galton-Fenzi, Benjamin Keith; Zika, Jan D.; Pellichero, Violaine; Uotila, Petteri (Frontiers in Marine Science, 2023)
Water mass transformation (WMT) around the Antarctic margin controls Antarctica Bottom Water formation and the abyssal limb of the global meridional overturning circulation, besides mediating ocean-ice shelf exchange, ice sheet stability and its contribution to sea level rise. However, the mechanisms controlling the rate of WMT in the Antarctic shelf are poorly understood due to the lack of observations and the inability of climate models to simulate those mechanisms, in particular beneath the floating ice shelves. We used a circum-Antarctic ocean-ice shelf model to assess the contribution of surface fluxes, mixing, and ocean-ice shelf interaction to the WMT on the continental shelf. The salt budget dominates the WMT rates, with only a secondary contribution from the heat budget. Basal melt of ice shelves drives buoyancy gain at lighter density classes (27.2 < σ_θ < 27.6 kg m^-3), while salt input associated with sea-ice growth in coastal polynyas drives buoyancy loss at heavier densities (σ_θ > 27.6). We found a large sensitivity of the WMT rates to model horizontal resolution, tides and topography within the Filchner-Ronne, East and West Antarctica ice shelf cavities. In the Filchner-Ronne Ice Shelf, an anticyclonic circulation in front of the Ronne Depression regulates the rates of basal melting/refreezing and WMT and is substantially affected by tides and model resolution. Model resolution is also found to affect the Antarctic Slope Current in both East and West Antarctica, impacting the on-shelf heat delivery, basal melt and WMT. Moreover, the representation of the ice shelf draft associated with model resolution impacts the freezing temperature and thus basal melt and WMT rates in the East Antarctica. These results highlight the importance of resolving small-scale features of the flow and topography, and to include the effects of tidal forcing, to adequately represent water mass transformations on the shelf that directly influence the abyssal global overturning circulation.